The Role Of human Resources in Sevice Marketing - Sukaini Sukaini, SE.M.M; Ruhaisal Ifna, S.Sos., M.M (International Journal of Economics, Business and Innovation Research, 2023)
Human Resources (HR) plays an important role in the success of a company. As the saying goes, human resources are a source of competitive advantage that is timeless by heat, not weathered by rain. Likewise achieving success in marketing services, of course, very much depends on the human resources that are owned The success of service marketing is highly dependent on human resources (HR) due to the direct involvement between service providers and consumers directly involved with consumers certainly need training, preparation, and high motivation to serve everyday consumers. In addition, sued to have the ability to be responsive in Fulfill the needs of consumers. HRs are also directly involved in the marketing process because, they must have a view of which large strategy marketing service company. Implementation from the whole aspect related to HR company service requires a commitment, way of respect, and implementation of the role optimally by whole member company service so that could acccurate operation and effectiveness performance.